TIGA KONSEP PENDIDIKAN MENURUT AL-QUR'AN - Mahani . (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2020)
This paper intends to describe three concepts of education according to the Qur'an which consist of ta'lim, ta'dib and tarbiyyah. Of course in the Koran these three words contain the meaning of education, but it needs to be emphasized that these words have their own meaning. This paper will reveal this by using a linguistic approach, the author will explain it comprehensively from various kinds of interpretations. The method used in this paper is the library research method or literature study. In conclusion, the concept of education according to the Koran is unique. The words at-tarbiyat, at-ta'lim, and at-ta'dib show a concept of education in these three concepts that complement each other and are included in educational goals that cannot be separated from one another.